TRANFORMATIONAL LEADERSHIP EFFECT ON THE MARKETING PERFORMANCE THROUGH MARKET ORIENTATION - Widiana, Muslichah Erma (Advances in Social Sciences Research Journal, 2017)
Regional Enterprise or so-called enterprises can play an important role for the region in particular and national development in general. As one source of local revenue or PAD in addition to tax and retribution, so that the management of enterprises require a serious and professional. Leadership is important to be discussed based on the consideration that, first, theoretically, leadership is positioned as the central factor that dominates, moving, directing, and coordinating various other factors within the organization. Leaders are needed for determining the continuity and development of business. Secondly, referring to previous research that leadership is a factor that significantly influence market orientation, organizational innovation and organizational performance. The purpose of this study was to: (1) test and analyze the effect of transformational leadership on market orientation; (2) to test and analyze the effect of transformational leadership on organizational innovation; (3) to test and analyze the effect of market orientation on performance marketing; (4) test and analyze the effect of innovation on the performance of marketing organizations; (5) to test and analyze the effect of market orientation on organizational innovation; (6) test and analyze the effect of transformational leadership on marketing performance.